Association of macronutrients intake distribution with osteoarthritis risk among adults in NHANES, 2013–2016 - Peng, Peng; Gao, Shihua; Xiao, Fangjun; He, Mincong; Fang, Weiuhua; Zhang, Yunqi; Wei, Qiushi (Frontiers in Nutrition, 2023)
Abstract The association between dietary macronutrient distribution and the risk of OA remains unknown. We aimed to evaluate how dietary macronutrient distribution was correlated with the risk of OA in US adults. We performed a cross-sectional study consisting of 7,725 participants from National Health and Nutrition Examination Survey (NHANES) 2013-2016. Dietary macronutrient intake and OA status were assessed by using dietary recall method and self-reported questionnaire, respectively. We evaluated the association between dietary macronutrient distribution and the risk of OA using multivariate regression models. We conducted the isocaloric substitution analysis using the multivariate nutrient density method. Higher percentage of energy intake from fat was associated with higher risk of OA (OR = 1.05 [95% CI,1.00, 1.09]; P = 0.034). No significant correlation was observed between the percentage of energy intake from carbohydrate or protein and risk of OA. Isocaloric substitution analysis revealed that only the substitution between fat and carbohydrate was significantly associated with the risk of OA (OR = 1.05 [95% CI, 1.003 to 1.09]; P = 0.037). Our findings suggested that a diet with low percentage of energy intake from fat may be beneficial in the prevention of OA. Further prospective cohort studies are needed to assess our results.